Simulasi, NDLC Simulasi Perancangan Infrastruktur Jaringan Komputer Pada Institut Teknologi Keling Kumang Menggunakan Pendekatan Network Development Life Cycle (NDLC) - Iip Yulianto Windra (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2022)
At this time, the development of information technology is growing very quickly, so the information needed is very easy to obtain via smartphones, laptops or computers connected to the internet. To support information technology, so that it can be used by the community or organization, a good computer network infrastructure is needed. The Keling Kumang Institute of Technology (ITKK) is a newly established university and will continue to grow, requiring computer network infrastructure that is in accordance with ITKK needs so that work in each field is more effective and efficient. In this study, using the Network Development Life Cycle (NDLC) method that can be used in designing computer network infrastructure that is in line with the organization's business processes. The application used for computer network infrastructure simulation in this study is GNS3.